Pediatric genitourinary injuries: 7-year experience at the largest tertiary referral hospital in Eastern part of Indonesia - Wirjopranoto S. (2023)
Introduction: The anatomical variations between children and adults render pediatric patients more prone to urogenital trauma. However, it is not known for certain whether children are more prone to genitourinary trauma than adults. The aim of the study is to scrutinize the characteristic of pediatric genitourinary trauma at, the largest tertiary hospital in Eastern part of Indonesia. Study design: The design of the study was analytic retrospective gathering medical records of all pediatric patients with urogenital trauma with total sampling. The number of patients, ages, genders, etiology, locations, and management were collected. Data was statistically analyzed using SPSS®, and p < 0.05 was considered statistically significant. Results: We found 13.5 (10–15.5) years as the median age in our 60 samples. Boy (75.00%), renal trauma (56.67%), abdominal and pelvic trauma (96.67%), traffic accident (91.67%), suprapubic catheterization (52.17%), and hemodynamically stable (91.67) was among the majority. We also found that non-operative management was in majority. Statistical analysis demonstrated significant differences for management and grade of injury (p < 0.05). Discussions: This is, to the best of our knowledge, the first study of genitourinary injuries in children who were treated at a tertiary hospital in Indonesia during the course of the 7-year research period. The limitations of this study are retrospective character and conducted in single institution. Conclusion: The highest incidence of pediatric urogenital trauma is renal trauma due to traffic accident, which often multitrauma. Future prospective multi-center studies should be done to corroborate the results.